Do juveniles who have committed sexual offenses have higher callous-unemotional traits compared to juveniles who have committed general offenses? A systematic review. - Ramião, Eduarda (2024)
The importance of assessing psychopathic traits in juveniles who have committed sexual offenses has been established in individuals who demonstrate a particularly severe and violent pattern of behavior. Additionally, the assessment of these traits in other juveniles might be relevant considering that higher levels of these traits represent an increased probability of the juvenile committing offenses. This study is a systematic review of the literature about the presence of callous-unemotional (CU) traits in juveniles who have committed sexual and non-sexual offenses, in order to ascertain eventual differences between these groups regarding the presence of CU traits. Studies were obtained from multiple databases, with predefined exclusion and inclusion criteria, according to PRISMA-P guidelines. A total of 18 studies were reviewed and included in the final analysis. The 18 studies used measures of CU traits and reported descriptive categories of CU traits in juveniles who have committed general offenses or juveniles who have committed sexual offenses. Meta-analytic procedures such as pooled means, pooled variances, and pooled standard deviations are presented in this study. The main conclusion obtained is that juveniles who have committed general offenses present higher levels of CU traits compared to juveniles who have committed sexual offenses. Although the review highlights limitations in the literature, the identification of these characteristics in different types of juveniles who have committed offenses is important to shed light on the phenomenon and develop interventions better suited to their characteristics. Recommendations for future research are also presented.